THE INFLUENCE OF RELIGIOSITY ON THE SELF-CONTROL OF INCARCERATED PERPETRATORS OF CHILD SEXUAL VIOLENCE AT YOGYAKARTA CLASS IIA CORRECTIONAL INSTITUTION - Wasistha, Chairunnisa Hewi; Hamzah, Imaduddin (Politeknik Ilmu Pemasyarakatan, 2025)
Inmates are individuals serving their sentences and undergoing rehabilitation in correctional institutions (Lapas). One important aspect of the inmate's social reintegration process is the ability to exercise self-control, particularly for perpetrators of child sexual abuse, who require a more in-depth personality development approach. This study aims to determine the extent to which religiosity influences self-control among inmates involved in child sexual abuse cases at the Class IIA Yogyakarta Prison. Religiosity is understood as an inner attitude and spiritual behavior that reflects an individual's closeness to religious teachings, which are believed to strengthen self-control and suppress negative impulses. A quantitative approach was applied by distributing questionnaires to inmates involved in child sexual abuse cases who served as the study sample. The variables used were religiosity and self-control, which have been tested for validity and reliability. The results showed a significant influence of religiosity on self-control. This finding underscores the importance of religious guidance as part of a rehabilitation strategy that can help inmates develop self-control and reduce the risk of relapse into deviant behavior.